Regulatory impact on the field of waste management in Ukraine: fiscal and budgetary dimensions - D. Kalinichenko; V. Holian; N. Medynska; I. Zivatkauskiene (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ)
It is substantiated that the slow pace of modernisation and reconstruction of the waste management industry in Ukraine is largely due to excessive unification of the set of fiscal, budgetary, credit, customs and compensation instruments of regulatory influence on the processes of generation, disposal, recycling and burial of industrial and household waste. It is established that the fiscal and budgetary dimensions of waste management regulation in Ukraine should be based on a set of regulatory approaches. This will stimulate the processes of intensifying resource conservation in secondary resource flows and ensure efficient use of the resource value of secondary natural raw materials. It has been found that accelerating the processes of using the resource value of household waste for energy purposes requires the use of financial incentives, primarily in terms of intensifying innovation, in particular, in the technology of producing gaseous and solid biological fuels. It is substantiated that the advanced foreign experience of using the tool of preferential taxation and financial and budgetary support for the implementation of resource conservation projects based on the utilization of the resource value of various types of waste has proven its value and can be fully used in the domestic practice of fiscal and budgetary regulation of the field of waste management. It was found that the differentiation of environmental tax rates for the generation and disposal of waste will increase the volume of waste use for the production of thermal and electrical energy by an order of magnitude, since lower tax rates for burning waste for energy production are a significant incentive for subjects of secondary resource use. It was established that the environmental tax for the placement of waste in specially designated places or facilities and for the generation of radioactive waste should be concentrated in special funds of public budgets of different taxonomic levels. These funds should be used for the development of the infrastructure for handling radioactive waste, for providing subsidies to consumers of energy from renewable sources and subsidies to subjects of industrial and economic activity, which implement projects of utilization of secondary natural raw materials for the purpose of production of various types of solid and gaseous biofuels. Key words: fiscal and budgetary dimensions, regulation, waste management, radioactive waste, resource conservation, investments.